Incidence of Achilles and patellar tendinopathy in adolescent elite athletes - Cassel, M.; Risch, L.; Intziegianni, K.; Mueller, J.; Stoll, J.; Brecht, P.; Mayer, F. (International Journal of Sports Medicine, 2018)
The study investigated the incidence of Achilles and patellar tendinopathy in adolescent elite athletes and non-athletic controls. Furthermore, predictive and associated factors for tendinopathy development were analyzed. The prospective study consisted of two measurement days (M1/M2) with an interval of 3.2±0.9 years. 157 athletes (12.1±0.7 years) and 25 controls (13.3±0.6 years) without Achilles/patellar tendinopathy were included at M1. Clinical and ultrasound examinations of both Achilles (AT) and patellar tendons (PT) were performed. Main outcome measures were incidence tendinopathy and structural intratendinous alterations (hypo-/hyperechogenicity, vascularization) at M2 [%]. Incidence of Achilles tendinopathy was 1% in athletes and 0% in controls. Patellar tendinopathy was more frequent in athletes (13%) than in controls (4%). Incidence of intratendinous alterations in ATs was 1-2% in athletes and 0% in controls, whereas in PTs it was 4-6% in both groups (p>0.05). Intratendinous alterations at M2 were associated with patellar tendinopathy in athletes (p=0.01). Intratendinous alterations at M1, anthropometric data, training amount, sports or sex did not predict tendinopathy development (p>0.05). Incidence of tendinopathy and intratendinous alterations in adolescent athletes is low in ATs and more common in PTs. Development of intratendinous alterations in PT is associated with tendinopathy. However, predictive factors could not be identified.